'A Sense of Myself as a Mother': An Exploration of Maternal Fantasies in the Experience of 'Circumstantial Childlessness'. Issue 1 (1st August 2017) - Tonkin, Lois
'Circumstantially childless' women (Cannold 2000 ) are those who have seen themselves as having a biological child or children at some point in their lives, but have come to — or are approaching — the end of their reproductive years without giving birth, for primarily social rather than biological reasons. The women who experience this form of childlessness are part of a growing demographic in Western countries, but the experience is not well understood. Using a detailed case example of one participant in a qualitative feminist psychosocial study of the experience of 26 circumstantially childless women in Aotearoa/New Zealand (Tonkin 2014 ), I draw on Hollway's (2015 ) work on the development of maternal subjectivity and Ettinger's (2006b ) concept of the 'matrixial' to try to make meaning of her apparently non-sensical 'sense of myself as a mother'. I suggest the term 'fantasy mother' as a further dimension of motherhood, as a way to take account of aspects of this experience that appear to cut across available discourses of maternity.